2022
DOI: 10.1111/obr.13515
|View full text |Cite
|
Sign up to set email alerts
|

Do eating behavior traits predict energy intake and body mass index? A systematic review and meta‐analysis

Abstract: Summary At present, it is unclear whether eating behavior traits (EBT) predict objectively measured short‐term energy intake (EI) and longer‐term energy balance as estimated by body mass index (BMI). This systematic review examined the impact of EBT on BMI and laboratory‐based measures of EI in adults ( ≥18 years) in any BMI category, excluding self‐report measures of EI. Articles were searched up until 28th October 2021 using MEDLINE, PsycINFO, EMBASE and Web of Science. Sixteen EBT were identified and the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 172 publications
2
13
1
2
Order By: Relevance
“…53 With regard to the positive controls, that have established relationships with BMI, disinhibition and emotional eating were positively associated with BMI. 25 Contrary to previous reports, 25 a negative association was found between the measure of restraint and BMI and note that other studies have also found weak evidence for this relationship. 54,55 It is plausible that the wording of the question (How often do you avoid eating tempting foods?)…”
Section: Measurecontrasting
confidence: 70%
See 3 more Smart Citations
“…53 With regard to the positive controls, that have established relationships with BMI, disinhibition and emotional eating were positively associated with BMI. 25 Contrary to previous reports, 25 a negative association was found between the measure of restraint and BMI and note that other studies have also found weak evidence for this relationship. 54,55 It is plausible that the wording of the question (How often do you avoid eating tempting foods?)…”
Section: Measurecontrasting
confidence: 70%
“…To establish the validity of the findings, this study also incorporated other psychological variables that have consistently been associated with BMI as "positive controls." 34 Psychological variables that have been positively associated with BMI are restrained eating (the intention to restrict food intake to prevent body weight gain), 25 emotional eating (consuming food due to feeling negative emotions), 25 disinhibited eating (the tendency to overeat in response to various stimuli), 25 and plate clearing (the tendency to clear one's plate when eating). 35 The data collection for this study coincided with the first wave of the SARS-CoV-2 pandemic lockdown in the UK (April-May 2020) and stringent stay-at-home restrictions were imposed on the UK population.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hal tersebut sesuai dengan hasil penelitian ini yaitu berdasarkan rata-rata skor item pertanyaan perilaku makan emotional eating (Tabel 2) diketahui bahwa keinginan makan sebagain besar subjek dipengaruhi oleh rasa (3,84±0,82;3,62±0,90) dan aroma (3,66±0,87) dari makanan. Hasil penelitian Dakin et al (2023) mengungkapkan bahwa keinginan makan makanan tertentu seperti makanan tinggi karbohidrat, makanan manis, makanan tinggi lemak berhubungan positif dengan "external eating" dan indeks masa tubuh. Berdasarkan penelitian ini diketahui bahwa rata-rata skor subjek dengan berat badan lebih dan obesitas lebih cenderung restrained eating (3,12±0,61 dan 2,83±0,61) dibanding subjek berstatus gizi normal (2,39±0,73) dan kurang (1,64±0,24).…”
Section: Hasil Dan Pembahasanunclassified